Corrosion-resistant overhead insulated cable

By introducing modified montmorillonite and silane coupling agent-treated corrosion-resistant masterbatch into the insulation layer of overhead insulated cables, the problem of insufficient corrosion resistance in existing technologies has been solved, and the high corrosion resistance and long service life design of cables have been achieved.

CN121439362APending Publication Date: 2026-01-30JIANYE CABLE GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511827995.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-05
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

The existing overhead insulated cables have insufficient corrosion resistance, which leads to a decrease in volume resistivity and an increase in dielectric loss. In severe cases, this can cause insulation breakdown and short circuits.

Method used

The structure adopts an inside-out design, including a conductor, a shielding layer, and an insulation layer. The insulation layer is composed of polyethylene, ethylene-vinyl acetate copolymer, corrosion-resistant masterbatch, calcium carbonate, light stabilizer, lubricant, and antioxidant. The corrosion-resistant masterbatch is treated with modified montmorillonite and silane coupling agent to improve the corrosion resistance of the insulation layer.

Benefits of technology

It significantly improves the corrosion resistance of overhead insulated cables, extends their service life, reduces the penetration rate of corrosive media, and enhances the density and oxidation resistance of the insulation layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of cables, and provides a corrosion-resistant aerial insulated cable which sequentially comprises a conductor, a shielding layer and an insulating layer from inside to outside. The conductor sequentially comprises an inner core layer and an outer core layer from inside to outside; the inner core layer is composed of six aluminum alloy conductors with the same diameter, and the outer core layer is composed of ten aluminum alloy conductors with the same diameter. The shielding layer is an aluminum foil shielding layer; the insulating layer comprises the following components in parts by weight: 70-80 parts of polyethylene, 20-35 parts of an ethylene-vinyl acetate copolymer, 15-20 parts of corrosion-resistant master batch, 25-30 parts of calcium carbonate, 1-2 parts of a light stabilizer, 2-3 parts of a lubricant, 1-2 parts of an antioxidant and 1-2 parts of a vulcanizing agent; the corrosion-resistant master batch is prepared from the following components in parts by weight: 65 to 70 parts of fluororubber, 5 to 9 parts of modified montmorillonite, 8 to 15 parts of ethylene-tetrafluoroethylene copolymer and 1 to 3 parts of sodium stearate. According to the technical scheme, the problem of poor corrosion resistance of the overhead insulated cable in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable technology, and more specifically, to a corrosion-resistant overhead insulated cable. Background Technology

[0002] Overhead insulated cables, as key equipment for transmitting medium and low voltage power in power systems, are widely used in urban distribution networks, industrial park transmission lines, and power supply networks in remote areas. Because they are exposed to outdoor natural environments or special industrial environments for extended periods, the requirements for corrosion resistance in overhead insulated cables are also higher. The insulation layer, acting as a barrier between the conductor and the external environment, is susceptible to corrosion and aging, leading to a decrease in volume resistivity, an increase in dielectric loss, and in severe cases, insulation breakdown and short circuits.

[0003] In current technologies, improving the corrosion resistance of cables mainly focuses on material selection. Corrosion-resistant cables typically use metal sheaths supplemented with anti-corrosion coatings, or directly add nanofillers to polymer substrates. However, they still have the disadvantage of insufficient corrosion resistance. Therefore, there is an urgent need for an overhead insulated cable with excellent corrosion resistance. Summary of the Invention

[0004] This invention proposes a corrosion-resistant overhead insulated cable, which solves the problem of poor corrosion resistance of overhead insulated cables in related technologies.

[0005] The technical solution of the present invention is as follows: This invention proposes a corrosion-resistant overhead insulated cable, which comprises, from the inside out, a conductor, a shielding layer, and an insulation layer; The conductor comprises an inner core layer and an outer core layer from the inside out; the inner core layer consists of six aluminum alloy wires of equal diameter, and the outer core layer consists of ten aluminum alloy wires of equal diameter. The shielding layer is an aluminum foil shielding layer; The insulating layer comprises the following components in parts by weight: 70-80 parts of polyethylene, 20-35 parts of ethylene-vinyl acetate copolymer, 15-20 parts of corrosion-resistant masterbatch, 25-30 parts of calcium carbonate, 1-2 parts of light stabilizer, 2-3 parts of lubricant, 1-2 parts of antioxidant, and 1-2 parts of vulcanizing agent. The corrosion-resistant masterbatch comprises the following components in parts by weight: 65-70 parts of fluororubber, 5-9 parts of modified montmorillonite, 8-15 parts of ethylene-tetrafluoroethylene copolymer, and 1-3 parts of sodium stearate. The modified montmorillonite is prepared by modifying montmorillonite with a silane coupling agent and spermine.

[0006] As a further technical solution, the preparation method of the corrosion-resistant masterbatch includes the following steps: A1. Dissolve the silane coupling agent in a mixed solution of ethanol and water, add spermine and montmorillonite, stir, filter, wash, and dry to obtain modified montmorillonite. A2. Fluororubber, the modified montmorillonite, ethylene-tetrafluoroethylene copolymer and sodium stearate are mixed, extruded and granulated to obtain corrosion-resistant masterbatch.

[0007] As a further technical solution, the mass ratio of the silane coupling agent, ethanol and water is 2:72:8~18; The mass ratio of montmorillonite, silane coupling agent, and spermine is 10:2:1~1.5.

[0008] In the corrosion-resistant overhead insulated cable of the present invention, the corrosion resistance of the overhead insulated cable can be further improved by adjusting the mass ratio of montmorillonite, silane coupling agent and spermine in the preparation of the corrosion-resistant masterbatch. When the mass ratio of montmorillonite, silane coupling agent and spermine is 10:2:1~1.5, the corrosion resistance of the overhead insulated cable can be further improved.

[0009] As a further technical solution, the silane coupling agent includes model KH550.

[0010] As a further technical solution, the calcium carbonate is modified calcium carbonate, and the preparation method of the modified calcium carbonate includes the following steps: dispersing calcium carbonate in water, adding oleyl alcohol polyoxyethylene ether and 2-amino-3-methylbutyric acid, stirring, filtering, washing, and drying to obtain modified calcium carbonate.

[0011] In the insulation layer of the corrosion-resistant overhead insulated cable of this invention, calcium carbonate is modified by using oleyl alcohol polyoxyethylene ether and 2-amino-3-methylbutyric acid in combination. This improves the compatibility of calcium carbonate with the polymer substrate, makes it more uniformly dispersed in the polymer substrate, makes the polymer substrate more dense, slows down the penetration rate of corrosive media, and thus improves the corrosion resistance of the manufactured overhead insulated cable.

[0012] As a further technical solution, the mass ratio of calcium carbonate, oleyl alcohol polyoxyethylene ether, and 2-amino-3-methylbutyric acid is 1:0.1:0.2~0.3; The mass ratio of calcium carbonate to water is 1:4~5.

[0013] As a further technical solution, the stirring temperature is 70~80℃.

[0014] As a further technical solution, the light stabilizer includes one or both of UV-1164 and UV-326.

[0015] In this invention, the insulation layer of the corrosion-resistant overhead insulated cable incorporates light stabilizers to prevent aging caused by ultraviolet radiation. Specifically, light stabilizer UV-1164, an o-hydroxyphenyltriazine class light stabilizer, releases the energy of absorbed ultraviolet photons as heat, exhibits low volatility, is not easily lost during cable processing, and can maintain stable performance over a long period. Light stabilizer UV-326, a benzotriazole compound, efficiently absorbs ultraviolet radiation with wavelengths of 270-380 nm, preventing polymer performance degradation due to ultraviolet radiation. Therefore, the addition of light stabilizers ensures the weather resistance of the manufactured overhead insulated cable.

[0016] As a further technical solution, the lubricant includes one or both of calcium stearate and polyethylene wax.

[0017] In the insulation layer of the corrosion-resistant overhead insulated cable of the present invention, the addition of calcium stearate and / or polyethylene wax as lubricants can reduce the friction between the melt and the equipment during mixing, extend the service life of the equipment, and reduce the resistance during polymer chain displacement, so that the components of the insulation layer are more uniformly fused, thus ensuring the corrosion resistance of the manufactured overhead insulated cable.

[0018] As a further technical solution, the antioxidant includes one or both of antioxidant 1076 and antioxidant 168.

[0019] The present invention extends the service life of the corrosion-resistant overhead insulated cable by adding antioxidant 1076 and / or antioxidant 168 to the insulation layer. Antioxidant 1076 is a hindered phenolic antioxidant, whose phenolic hydroxyl groups can terminate the oxidation chain reaction; antioxidant 168 is a phosphite antioxidant, which can decompose the hydroperoxides generated in the oxidation chain reaction, thereby interrupting the chain reaction. Therefore, the addition of antioxidant 1076 and / or antioxidant 168 can effectively inhibit the oxidative degradation of the insulation layer and extend the service life of the manufactured overhead insulated cable.

[0020] As a further technical solution, the vulcanizing agent includes sulfur.

[0021] This invention also proposes a method for preparing a corrosion-resistant overhead insulated cable, comprising the following steps: S1. Mix the components of the insulating layer, extrude them to obtain the insulating layer material; S2. A shielding layer is set outside the conductor, and the insulating material is wrapped around the shielding layer and vulcanized to obtain a corrosion-resistant overhead insulated cable.

[0022] As a further technical solution, the mixing temperature is 100~110℃ and the time is 20~25min.

[0023] The working principle and beneficial effects of this invention are as follows: In this invention, the corrosion resistance of overhead insulated cables can be improved by adding corrosion-resistant masterbatch to the insulation layer. Specifically, the CF bonds of the fluororubber in the corrosion-resistant masterbatch can directly resist chemical erosion by acidic and alkaline media, preventing the molecular chains of the insulation layer from being corroded and broken. Furthermore, the modification of montmorillonite using a combination of spermine and silane coupling agents increases the compatibility of montmorillonite with fluororubber, further enhancing the corrosion resistance of the prepared corrosion-resistant masterbatch, thereby improving the corrosion resistance of the manufactured overhead insulated cables. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] In the following embodiments and comparative examples, the conductor comprises an inner core layer and an outer core layer from the inside out; the inner core layer consists of six aluminum alloy wires of equal diameter, and the outer core layer consists of ten aluminum alloy wires of equal diameter.

[0026] The fluororubber is designated BR9151 and manufactured by Shanghai Kazila Chemical Co., Ltd.; the ethylene-tetrafluoroethylene copolymer is designated Z-8820X; the montmorillonite is designated PGW and manufactured by Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the calcium carbonate has a particle size of 30nm; the polyethylene is designated 2426H; and the ethylene-vinyl acetate copolymer is designated EA28400.

[0027] Example 1 The preparation method of corrosion-resistant masterbatch includes the following steps: A1. By weight, dissolve 2 parts of silane coupling agent KH550 in a mixed solution of 72 parts of ethanol and 8 parts of water, add 0.8 parts of spermine and 10 parts of montmorillonite, stir, filter, wash, and dry to obtain modified montmorillonite. A2. By weight, 65 parts of fluororubber, 5 parts of modified montmorillonite, 8 parts of ethylene-tetrafluoroethylene copolymer, and 1 part of sodium stearate are mixed, extruded and granulated to obtain corrosion-resistant masterbatch. A method for preparing corrosion-resistant overhead insulated cables includes the following steps: S1. By weight, 70 parts of polyethylene, 20 parts of ethylene-vinyl acetate copolymer, 15 parts of corrosion-resistant masterbatch, 25 parts of calcium carbonate, 1 part of light stabilizer UV-1164, 2 parts of calcium stearate, 1 part of antioxidant 1076, and 1 part of sulfur are mixed at 100°C for 25 minutes and then extruded to obtain the insulating layer material. S2. An aluminum foil shielding layer is set outside the conductor, and the insulation material is extruded and wrapped around the aluminum foil shielding layer. After vulcanization, a corrosion-resistant overhead insulated cable is obtained.

[0028] Example 2 The preparation method of corrosion-resistant masterbatch includes the following steps: A1. By weight, dissolve 2 parts of silane coupling agent KH550 in a mixed solution of 72 parts of ethanol and 14 parts of water, add 0.8 parts of spermine and 10 parts of montmorillonite, stir, filter, wash, and dry to obtain modified montmorillonite. A2. By weight, 70 parts of fluororubber, 9 parts of modified montmorillonite, 15 parts of ethylene-tetrafluoroethylene copolymer, and 3 parts of sodium stearate are mixed, extruded and granulated to obtain corrosion-resistant masterbatch. A method for preparing corrosion-resistant overhead insulated cables includes the following steps: S1. By weight, 80 parts of polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 20 parts of corrosion-resistant masterbatch, 30 parts of calcium carbonate, 1 part of light stabilizer UV-1164, 1 part of light stabilizer UV-326, 1.5 parts of polyethylene wax, 1.5 parts of calcium stearate, 1 part of antioxidant 168, 1 part of antioxidant 1076, and 2 parts of sulfur are mixed at 110°C for 20 minutes and then extruded to obtain the insulating layer material. S2. An aluminum foil shielding layer is set outside the conductor, and the insulation material is extruded and wrapped around the aluminum foil shielding layer. After vulcanization, a corrosion-resistant overhead insulated cable is obtained.

[0029] Example 3 The preparation method of corrosion-resistant masterbatch includes the following steps: A1. By weight, dissolve 2 parts of silane coupling agent KH550 in a mixed solution of 72 parts of ethanol and 18 parts of water, add 0.8 parts of spermine and 10 parts of montmorillonite, stir, filter, wash, and dry to obtain modified montmorillonite. A2. By weight, 68 parts of fluororubber, 8 parts of modified montmorillonite, 12 parts of ethylene-tetrafluoroethylene copolymer, and 2 parts of sodium stearate are mixed, extruded and granulated to obtain corrosion-resistant masterbatch. A method for preparing corrosion-resistant overhead insulated cables includes the following steps: S1. By weight, 75 parts of polyethylene, 30 parts of ethylene-vinyl acetate copolymer, 18 parts of corrosion-resistant masterbatch, 28 parts of calcium carbonate, 1.5 parts of light stabilizer UV-326, 2.5 parts of polyethylene wax, 1.5 parts of antioxidant 168, and 1.5 parts of sulfur are mixed at 105°C for 22 minutes and then extruded to obtain the insulating layer material. S2. An aluminum foil shielding layer is set outside the conductor, and the insulation material is extruded and wrapped around the aluminum foil shielding layer. After vulcanization, a corrosion-resistant overhead insulated cable is obtained.

[0030] Example 4 The only difference between this embodiment and Example 3 is the addition of 1 part spermine.

[0031] Example 5 The only difference between this embodiment and Example 3 is the addition of 1.2 parts of spermine.

[0032] Example 6 The only difference between this embodiment and Example 3 is the addition of 1.5 parts of spermine.

[0033] Example 7 The only difference between this embodiment and Example 3 is the addition of 1.7 parts of spermine.

[0034] Example 8 The difference between this embodiment and Example 5 is that calcium carbonate is replaced with modified calcium carbonate. The preparation method of modified calcium carbonate includes the following steps: dispersing calcium carbonate in 4 times its mass of water, adding oleyl alcohol polyoxyethylene ether and 2-amino-3-methylbutyric acid, stirring at 70°C, filtering, washing, and drying to obtain modified calcium carbonate, wherein the mass ratio of calcium carbonate, 2-amino-3-methylbutyric acid and oleyl alcohol polyoxyethylene ether is 1:0.1:0.2.

[0035] Example 9 The difference between this embodiment and Example 5 is that calcium carbonate is replaced with modified calcium carbonate. The preparation method of modified calcium carbonate includes the following steps: dispersing calcium carbonate in 5 times its mass of water, adding oleyl alcohol polyoxyethylene ether and 2-amino-3-methylbutyric acid, stirring at 80°C, filtering, washing, and drying to obtain modified calcium carbonate, wherein the mass ratio of calcium carbonate, 2-amino-3-methylbutyric acid and oleyl alcohol polyoxyethylene ether is 1:0.1:0.3.

[0036] Comparative Example 1 The only difference between this comparative example and Example 3 is the preparation method of the corrosion-resistant masterbatch, which includes the following steps: A1. By weight, dissolve 2 parts of silane coupling agent KH550 in a mixed solution of 72 parts of ethanol and 18 parts of water, add 10 parts of montmorillonite, stir, filter, wash, and dry to obtain modified montmorillonite. A2. By weight, 68 parts of fluororubber, 8 parts of modified montmorillonite, 12 parts of ethylene-tetrafluoroethylene copolymer, and 2 parts of sodium stearate are mixed, extruded and granulated to obtain corrosion-resistant masterbatch.

[0037] Comparative Example 2 The only difference between this comparative example and Example 3 is the preparation method of the corrosion-resistant masterbatch, which includes the following steps: A1. Dissolve 0.8 parts by weight of spermine in a mixed solution of 72 parts by weight of ethanol and 18 parts by weight of water, add 10 parts by weight of montmorillonite, stir, filter, wash, and dry to obtain modified montmorillonite. A2. By weight, 68 parts of fluororubber, 8 parts of modified montmorillonite, 12 parts of ethylene-tetrafluoroethylene copolymer, and 2 parts of sodium stearate are mixed, extruded and granulated to obtain corrosion-resistant masterbatch.

[0038] Comparative Example 3 The only difference between this comparative example and Example 3 is that the modified montmorillonite is replaced with montmorillonite.

[0039] Comparative Example 4 The only difference between this comparative example and Example 3 is the preparation method of the corrosion-resistant overhead insulated cable; A method for preparing corrosion-resistant overhead insulated cables includes the following steps: S1. By weight, 13.6 parts of fluororubber, 2.4 parts of ethylene-tetrafluoroethylene copolymer, 0.4 parts of sodium stearate, 1.6 parts of modified montmorillonite, 75 parts of polyethylene, 30 parts of ethylene-vinyl acetate copolymer, 28 parts of calcium carbonate, 1.5 parts of light stabilizer UV-326, 2.5 parts of polyethylene wax, 1.5 parts of antioxidant 168, and 1.5 parts of sulfur are mixed and extruded to obtain an insulating layer material. S2. An aluminum foil shielding layer is set outside the conductor, and the insulation material is extruded and wrapped around the aluminum foil shielding layer. After vulcanization, a corrosion-resistant overhead insulated cable is obtained.

[0040] The performance of the insulation layers of the corrosion-resistant overhead insulated cables prepared in Examples 1-9 and Comparative Examples 1-4 were tested respectively: Corrosion resistance: The tensile strength was determined according to the test methods specified in GB / T 2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables", and the corrosion resistance test was carried out. The specific test method is as follows: The sample was immersed in 20wt% hydrochloric acid aqueous solution at 25℃ for 30 days and then taken out. Its tensile strength was measured and the tensile strength change rate was calculated. The tensile strength change rate (%) = (tensile strength after test / tensile strength before test - 1) × 100%. The specimen was a dumbbell specimen with a thickness of 0.8 mm. The results are shown in Table 1 below.

[0041] Table 1 Performance Test Results

[0042] By comparing the data of Example 3 and Comparative Example 4, it was found that the tensile strength of the overhead insulated cable prepared by Example 3, which pre-prepared corrosion-resistant masterbatch, was higher than that of Comparative Example 4, and the rate of change of tensile strength was smaller than that of Comparative Example 4. This indicates that the corrosion-resistant masterbatch prepared in this application significantly improves the corrosion resistance of the overhead insulated cable.

[0043] By comparing the data of Example 3 and Comparative Examples 1-3, it was found that the tensile strength of the overhead insulated cable prepared by Example 3, which modified montmorillonite by using a combination of spermine and silane coupling agent, was greater than that of Comparative Examples 1-3, and the rate of change of tensile strength was smaller than that of Comparative Examples 1-3. This indicates that the corrosion resistance of the overhead insulated cable can be further improved by modifying montmorillonite by using a combination of spermine and silane coupling agent.

[0044] By comparing the data from Examples 3 to 7, the tensile strength of the overhead insulated cables prepared in Examples 5 and 6 is greater than that in Examples 3 and 7, and the rate of change of tensile strength is smaller than that in Examples 3 and 7. This indicates that by adjusting the mass ratio of montmorillonite, silane coupling agent, and spermine, and when the mass ratio of montmorillonite, silane coupling agent, and spermine is 1:2:1 to 1.5, the corrosion resistance of the overhead insulated cables can be further improved.

[0045] By comparing the data from Examples 3 and 8-9, it was found that the tensile strength of the overhead insulated cables prepared by modifying montmorillonite with a combination of oleyl alcohol polyoxyethylene ether and 2-amino-3-methylbutyric acid in Examples 8-9 was greater than that in Example 3, and the rate of change of tensile strength was smaller than that in Example 3. This indicates that modifying montmorillonite with a combination of oleyl alcohol polyoxyethylene ether and 2-amino-3-methylbutyric acid can further improve the corrosion resistance of overhead insulated cables.

[0046] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A corrosion resistant aerial insulated electrical cable, characterized in that, The conductor comprises, from inside to outside, a conductor, a shielding layer and an insulating layer; The conductor comprises, from inside to outside, an inner core layer and an outer core layer; the inner core layer is composed of six equal-diameter aluminum alloy wires, and the outer core layer is composed of ten equal-diameter aluminum alloy wires; The shielding layer is an aluminum foil shielding layer; The insulating layer comprises the following components in parts by weight: polyethylene 70-80 parts, ethylene-vinyl acetate copolymer 20-35 parts, corrosion-resistant master batch 15-20 parts, calcium carbonate 25-30 parts, light stabilizer 1-2 parts, lubricant 2-3 parts, antioxidant 1-2 parts, and vulcanizing agent 1-2 parts; The corrosion-resistant master batch comprises the following components in parts by weight: fluoroelastomer 65-70 parts, modified montmorillonite 5-9 parts, ethylene-tetrafluoroethylene copolymer 8-15 parts, and sodium stearate 1-3 parts; The modified montmorillonite is prepared by modifying montmorillonite with a silane coupling agent and spermine.

2. The corrosion resistant aerial bundled conductor cable of claim 1, wherein, The preparation method of the corrosion-resistant master batch comprises the following steps: A1, dissolving the silane coupling agent in a mixed solution of ethanol and water, adding spermine and montmorillonite, stirring, filtering, washing, and drying to obtain modified montmorillonite; A2, mixing and kneading fluoroelastomer, the modified montmorillonite, ethylene-tetrafluoroethylene copolymer and sodium stearate, and then extruding and granulating to obtain the corrosion-resistant master batch.

3. A corrosion resistant aerial bundle cable according to claim 2, wherein, The mass ratio of the silane coupling agent, ethanol and water is 2:72:8-18; The mass ratio of the montmorillonite, silane coupling agent and spermine is 10:2:1-1.

5.

4. The corrosion resistant aerial bundle conductor of claim 2, wherein, The type of the silane coupling agent includes KH550.

5. The corrosion resistant aerial insulated cable of claim 1, wherein, The calcium carbonate is modified calcium carbonate, and the preparation method of the modified calcium carbonate comprises the following steps: dispersing calcium carbonate in water, adding oleyl polyoxyethylene ether and 2-amino-3-methylbutyric acid, stirring, filtering, washing, and drying to obtain the modified calcium carbonate.

6. A corrosion resistant aerial bundle conductor cable according to claim 5, wherein, The mass ratio of the calcium carbonate, oleyl polyoxyethylene ether and 2-amino-3-methylbutyric acid is 1:0.1:0.2-0.3; The mass ratio of the calcium carbonate and water is 1:4-5.

7. A corrosion resistant aerial bundle conductor cable according to claim 5, wherein, The stirring temperature is 70-80℃.

8. The corrosion resistant aerial insulated cable of claim 1, wherein, The type of the light stabilizer includes one or both of UV-1164 and UV-326.

9. The corrosion resistant aerial insulated cable of claim 1, wherein, The lubricant includes one or both of calcium stearate and polyethylene wax.

10. The corrosion resistant aerial insulated cable of claim 1, wherein, The antioxidant includes one or both of antioxidant 1076 and antioxidant 168.